PROBLEMATIKA PEMENUHAN HAK KONSUMEN DALAM PERATURAN PEMERINTAH NOMOR 80 TAHUN 2019 TENTANG PERDAGANGAN MELALUI SISTEM ELEKTRONIK SERTA PERLINDUNGAN KONSUMEN ATAS POP-UP STORE - Alfa Edha Firmansyah; Suraji . (Fakultas Hukum Universitas Sebelas Maret, 2024)
This article examines the problems of consumer protection against consumer rights with pop-up stores as an alternative to online shopping that can be done in terms of overcoming violations of consumer rights and solutions that can be done to protect consumers against the disadvantages of online shopping. This research is a normative legal research that is descriptive and applied with a legal approach (statue approach), conceptual approach (conceptual approach) and historical approach (historical approach). Types of legal materials include primary and secondary legal materials. The technique of collecting legal materials is a literature study which will then be studied deductively using a syllogistic logic. The results showed the problems of consumer protection for the rights of consumers to shop online and pop-up stores, first, in that consumers cannot directly test, try, see or touch the goods to be ordered when shopping online. Second, the unclear status of legal subjects of business actors. Third, unclear information about the products offered in the form of misleading advertisements. Fourth, the imposition of an unbalanced risk on guaranteed delivery of goods. Fifth, borderless cross-border transactions raise questions about the mechanism for fulfilling consumer rights and obligations of business actors in transactions between countries. Sixth, there are no statutory provisions or implementing provisions for the pop-up store trading model or O2O business (online to offline or offline to online).